Dvaravati Sri Nakhon Pathom: Historical and Archaeological Development - Pichet Samutvaranont (Journal of Contemporary Buddhist Society = JCBS, 2023)
The writing of the book “Dvaravati Sri Nakhon Pathom: Historical and Archaeological Development” is a compilation of both primary and secondary sources in history, archaeology, literature, and ethnographic studies related to the ancient city of Nakhon Pathom, also known as Nakhon Chai Si, and its present-day counterpart. This book serves as a resource for future generations who are interested in studying and understanding the historical background, way of life, beliefs, and thought systems of the people of Nakhon Pathom. By fostering an awareness of ancestral roots and cultural heritage, the book provides insights into the origins of Thai traditions and customs, offering an understanding of how past civilizations evolved. This knowledge nurtures a sense of pride and appreciation for one’s homeland. Additionally, it serves as a foundation for the exchange of knowledge, conservation, development, and the continuation of both national and local cultural heritage in a sustainable manner. Regarding challenges and areas requiring further improvement, the reviewer suggests that integrating efforts and collaborative problem-solving would be the most effective approach to achieving the objectives of all involved parties. Such efforts would ultimately instill a deep sense of pride among the people of Nakhon Pathom. This book is an invaluable resource for those interested in exploring the history of Nakhon Pathom, a city once recognized as a significant center of Buddhism during the Dvaravati period.